DETERMINANTS OF PREGNANCY COMPLICATIONS: AN ANALYSIS OF INDONESIAN DEMOGRAPHIC AND HEALTH SURVEY DATA (IDHS) 2017 - Tsuraya Salsabila, Salma; Widiasih, Restuning; Mamuroh, Lilis (Jurnal Keperawatan Karya Bhakti, 2025)
Indonesia is the third country with the highest maternal mortality rate (MMR) in Southeast Asia and has not yet reached the SDGs target. Many maternal deaths in Indonesia are caused by pregnancy complications. Information on factors that influence pregnancy complications in Indonesia is still limited, especially those that use large amounts of data. The purpose of this study was to analyse the factors that influence the occurrence of pregnancy complications in provinces with different MMR levels, namely Papua, West Java and DKI Jakarta. This study used a descriptive correlational design using secondary data from the 2017 Indonesian Demographic and Health Surveys (IDHS). Data were obtained from the official website, dhsprogram.com. The population in the study was women of reproductive age (WRA) in Indonesia. Sampling used cluster sampling technique. Inclusion criteria were WUS aged 15-49 years who had or were experiencing pregnancy in the last 5 years when the survey was conducted, namely 1,451 samples. The analysis conducted was univariate analysis to describe the proportion of pregnancy complications and data distribution based on the independent variables studied and bivariate chi square analysis to see the relationship between the independent and dependent variables. The findings showed that the majority of WRA from the three provinces experienced uncomplicated pregnancies. Bivariate analysis showed no significant association between age, parity, birth interval, education level, smoking lifestyle, antenatal care visits, and husband support with pregnancy complications among women in Papua and DKI Jakarta provinces. Meanwhile, in West Java Province there was a significant association between smoking lifestyle and pregnancy complications, however, the other six factors were not associated. The study concluded that pregnancy complications are influenced by other factors that more strongly affect pregnancy complications. It is recommended for future research to examine other variables that have not been studied in this study. In addition, strategic planning is also needed to reduce the number of high-risk pregnant women in the provinces of Papua, West Java, and DKI Jakarta.